Obywatel? Jaki obywatel? Świadectwo mennictwa rzymskiego czasów karakalli - Kluczek, Agata Aleksandra (In Gremium. Studies in History, Culture and Politics, 2013)
A citizen? What type of a citizen? Evidence of Roman mintage at Caracalla times The subject of consideration is the issue of graphic reflection of the nature of Roman citizens in the images placed at the reverse of Roman coins. The citizen’s duties, his privileges as well as his civic activity were depicted at these coins through a filter of the omnipresent in the circles of central and local authorities socio-political ideology, influencing the content of iconography of the empire and provincial mintage. Such a perspective allows to emphasize the role of numismatic sources in the recognition of declared, not factual, place of the citizen in the Roman state at the time of Empire. It furthers induces reflection over self-identification of the ancient as citizens as well as over the relationship between the subjects and the Emperor. The mintage at Caracalla times serves as a pretext to make generalizations and summaries which both concern wider time period of the first three centuries of the Empire.